2010
DOI: 10.1038/ki.2010.332
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and non-traditional strategies to optimize catheter function: go with more flow

Abstract: In the United States, over 340,000 patients have end-stage renal disease treated by hemodialysis (HD) and are dependent on a reliable vascular access. In over 80% of patients initiating HD, this access is the central venous catheter (CVC). Although the CVC has many advantages that make it desirable for dialysis initiation-ease of insertion, unnecessary maturation time, and availability for immediate use-it is not without significant disadvantages. The substantial morbidity and mortality associated with CVC use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 111 publications
1
33
0
2
Order By: Relevance
“…Poor initial CVC positioning or kinking could lead to poor blood flows that usually result in early failure of the CVC (<7 days) following insertion [6]. In our survey, catheter changes due to malfunction were double the rate of changes due to infection, with 2.1 and 0.9 CVC changes/1000 catheter days for malfunction and infection, respectively.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Poor initial CVC positioning or kinking could lead to poor blood flows that usually result in early failure of the CVC (<7 days) following insertion [6]. In our survey, catheter changes due to malfunction were double the rate of changes due to infection, with 2.1 and 0.9 CVC changes/1000 catheter days for malfunction and infection, respectively.…”
Section: Discussionmentioning
confidence: 54%
“…Although the use of anaesthetic creams and other agents has helped to reduce the pain of venipuncture, CVCs do offer needle-free dialysis. The benefits must be balanced against the increased risks of catheter malfunction with poor blood flows, catheterrelated infection episodes, as well as restrictions on bathing and swimming [6,7]. CVCs might also contribute to increased inflammation independent of infection [8].…”
Section: Introductionmentioning
confidence: 99%
“…13 The increased rates of early noninfectious catheter complications have also been described. 14 Xue et al reported use of tissue plasminogen activator and rate of catheter replacement use of 6.38 and 1.05, respectively, per 1000 accessdays over 1 year, with a higher rate of intervention in the first 90 days. 9 Strengths of this investigation include the ascertainment of longitudinal data and a large cohort (n57140) of randomly selected incident patients starting hemodialysis for the first time from the DOPPS.…”
mentioning
confidence: 99%
“…They also found that by precisely measuring the volume of the catheter with saline (which was on average <2 mL) prior to dalteparin administration, they could reduce both the aPTT and risk of bleeding [12]. This finding has been supported in both in vitro [13,14] and in vivo studies [11,[15][16][17][18]. Proposed mechanisms for systemic spillage included variable catheter volume, catheter design with side holes, and laminar flow [11].…”
Section: Discussionmentioning
confidence: 80%